Condition factor of Astyanax intermedius Eigenmann, 1908 (OSTEICHTHYES, CHARACIDAE) parasitised by Paracymothoa astyanaxi Lemos de Castro, 1955 (CRUSTACEA, CYMOTHOIDAE) in the Grande River, Serra do Mar State Park - Santa Virgínia Unit, São Paulo, Brazil - Gomiero, LM [UNESP]; Souza, UP [UNESP]; Braga, Francisco Manoel de Souza [UNESP] (Instituto Internacional de Ecologia, 2012)
Foram analisados a relação peso-comprimento e o fator de condição de Astyanax intermedius parasitados ou não pelo isópode Paracymothoa astyanaxi. A relação peso-comprimento foi estimada para fêmeas, machos e imaturos, e sazonalmente tanto para os peixes quanto para o parasito, por meio da expressão P = aCb. O fator de condição dos exemplares não parasitados diferiu sazonalmente e entre os sexos, contrastando com os valores do fator de condição dos peixes parasitados, que não apresentaram diferenças sazonais e entre os sexos. O fator de condição dos exemplares não parasitados foi sempre maior do que o dos exemplares parasitados. Os exemplares de Astyanax intermedius parasitados não passaram pelas mesmas condições bióticas dos indivíduos não parasitados, apresentando um fator de condição semelhante ao longo do ano. Conclui-se que o parasitismo por P. astyanaxi atua de forma deletéria na população desse hospedeiro, podendo causar alterações nas dinâmicas reprodutiva e alimentar dos exemplares parasitados em razão da baixa condição corpórea.

In this work the length-weight relationship and the condition factor of Astyanax intermedius parasitised and not by Paracymothoa astyanaxi were analysed in the Grande River. The length-weight relationship was estimated for females, males and immatures, and seasonally for the fishes and the parasites through the expression W = aLb. The condition factor of non-parasitised specimens differed seasonally and between sexes, contrasting with the results for parasitised fishes which showed no differences between sexes and season. The condition factor of non-parasitised specimens was higher than that of the parasitised fishes. Specimens of Astyanax intermedius parasitised do not have the same biotic conditions compared to non-parasitised individuals, in which the condition factor was similar over the years. In conclusion, parasitism by P. astyanaxi has deleterious effects on this host population which may cause changes in the reproductive and food dynamics of parasitised specimens due to low body conditions.
Fator de condição de Astyanax intermedius Eigenmann, 1908 (OSTEICHTHYES, CHARACIDAE) parasitados por Paracymothoa astyanaxi Lemos de Castro, 1955 (CRUSTACEA, CYMOTHOIDAE) no Rio Grande, Núcleo Santa Virgínia, Parque Estadual da Serra do Mar, São Paulo, Brasil
Keywords: parasitismo; fator de condição; relação peso-comprimento; parasitism; condition factor; length-weight relationship